Inconsistent phenotypic differentiation at physiological traits in Norway spruce (Picea abies Karst.) provenances under contrasting water regimes - Gömöry Dušan; Ditmarová Ľubica; Hrivnák Matúš; Jamnická Gabriela; Konôpková Alena; Krajmerová Diana; Kurjak Daniel; Marešová Jana (Central European Forestry Journal, 2023)
Norway spruce is expected to suffer from drought stress and other manifestations of climate change. This study relies on a manipulative experiment with drought-stressed and well-watered (control) seedlings, comprising five provenances of Norway spruce distributed along a steep elevational transect from 550 to 1,280 m a.s.l. within the natural range. Seedlings were subjected to measurement of physiological traits (content of phytohormones and monoterpenes, slow and fast chlorophyll a fluorescence kinetics, gas exchange, hyperspectral indices), and genotyping at 8 nuclear microsatellite loci. Comparison of the coefficient of differentiation at neutral loci (FST) vs. differentiation at phenotypic traits (PST) was used to identify traits underlying divergent selection. In total, 18 traits exhibited a significant PST – FST difference. However, the consistency in differentiation patterns between drought-stressed and control plants was limited, only three traits exhibited signals of selection under both treatments. This outcome indicates that the identified differentiation patterns can only be interpreted in the context of environmental setup of the experiment, and highlights the importance of common gardens in adaptation research, as they allow both elimination of environment-induced phenotypic variation and studying genotype-by-environment interaction in physiological responses to environmental stresses.